2021
DOI: 10.3390/nu13072211
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverage Consumption Status and Its Association with Childhood Obesity among Chinese Children Aged 6–17 Years

Abstract: Objective: There is a remarkable growth in sugar-sweetened (SSB) production and obesity prevalence among school-aged children in China. This paper describes SSB consumption and its association with obesity among Chinese children aged 6–17 years in 2012. Methods: in total, 25,553 children aged 6~17 years enrolled in the China Nutrition and Health Surveillance 2010–2013 were included in this study. Data of SSB consumption frequency and quantity were obtained from a food frequency questionnaire, and the children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…We also found the top three contributors to beverage consumption and sugar intake were protein beverages, fruit/vegetable juices and beverage and carbonated beverages. A study in China found the similar result that juice and milk beverages were more popular than carbonated and tea beverages among Chinese children [10]. Protein beverages in our study were not the beverages with the most sugar content, but it was the most popular beverage among students, which indicated the intake of protein beverages was the highest.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We also found the top three contributors to beverage consumption and sugar intake were protein beverages, fruit/vegetable juices and beverage and carbonated beverages. A study in China found the similar result that juice and milk beverages were more popular than carbonated and tea beverages among Chinese children [10]. Protein beverages in our study were not the beverages with the most sugar content, but it was the most popular beverage among students, which indicated the intake of protein beverages was the highest.…”
Section: Discussionsupporting
confidence: 72%
“…Frequent intake of excessive SSBs is strongly associated with obesity [4], diabetes [5], hypertension [6] and dental caries [7] among children due to the high sugar and energy content and little nutritional value of SSBs. With the rapid urbanization, economic improvement and increasing westernized diet in China, there were 66.6% of the children consuming SSBs in 2013 [8], and the proportion of children who consumed SSBs more than once per week increased greatly from 14.2% in 2002 [9] to 79.2% in 2012 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension in rats fed fructose plus high-salt diets has also been reported using telemetry, albeit with more modest increases in blood pressure [102][103][104]. The fructose intake by Asian populations is generally less than that by individuals from Europe or America, but more recent findings suggest a troubling rise, particularly in SSB consumption by adolescents [91,94,95,98]. This would suggest that preclinical data regarding fructose, either with or without high-salt intake, will be more relevant to societies worldwide.…”
Section: Preclinical Data On Dietary Fructose High Salt and Blood Pre...mentioning
confidence: 85%
“…However, SSB consumption among children has increased dramatically in recent decades. According to data from the 2010s, children from the United States had 155 kcal intake from SSBs daily [ 32 ], and 6–17-year-old children in China had an average SSBs consumption of 181 g/day and 2.2 times per week in 2020 [ 33 ]. Only 35.2% of children in our study reported no SSB consumption in the last week, which is lower than the data of 2020 [ 33 ], confirming the increasing trend of SSBs in China.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the 2010s, children from the United States had 155 kcal intake from SSBs daily [ 32 ], and 6–17-year-old children in China had an average SSBs consumption of 181 g/day and 2.2 times per week in 2020 [ 33 ]. Only 35.2% of children in our study reported no SSB consumption in the last week, which is lower than the data of 2020 [ 33 ], confirming the increasing trend of SSBs in China. In the last 10 years, only data from the North American area reported a decrease in SSBs [ 34 ], while data from eastern China 2019 showed that about 40% of high school children consumed SSBs once per week [ 35 ].…”
Section: Discussionmentioning
confidence: 99%